Pendampingan Diversifikasi Pangan Berbasis Olahan Limbah Jagung Bernilai Ekonomis pada Sekolah Dasar Daerah Perbatasan : Implementasi Ekonomi Sirkular dalam Bingkai Projek P5 - Jewarut, Siprianus; Usman, Usman; Usman, Margaretha Lidya Sumarni; Melati, Felisitas Viktoria (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to improve the knowledge and skills of participants in implementing a circular economy through mentoring food diversification based on processed corn waste with economic value within the framework of the P5 project. Participants in the implementation of this mentoring amounted to 188 people consisting of high and low-grade students at SDN 01 Bengkayang, West Kalimantan. The implementation of this community service uses a mentoring method with cycle stages, where each cycle is evaluated. The results of this community service show that 75% of partners understand the material and stages of mentoring. In addition, 70% of partners have good skills. This shows that the mentoring process that has been carried out can improve the knowledge and skills of partners in implementing a circular economy through mentoring food diversification based on processed corn waste with economic value within the framework of the P5 project.